Testing Web Applications with State Objects. - VAN DEURSEN, ARIE (Communications of the ACM, 2015)
The article discusses a state-based generalization of page objects or state objects. It describes the features of several tools, including WebDriver, a tool used for testing Web applications. Statecharts from the Unified Modeling Language (UML) are used in order to model Web application navigation. Inspection methods and trigger methods are identified as two types of methods for each state object. In addition, the article provides instructions on logging with conditional events, registering a new user and logging into an application.